Nanoparticles in association with antimicrobial peptides (NanoAMPs) as a promising combination for agriculture development - Maximiano, Mariana Rocha; Rios, Thuanny Borba; Campos, Marcelo Lattarulo; Prado, Guilherme Souza; Dias, Simoni Campos; Franco, Octávio Luiz (Frontiers in Molecular Biosciences, 2022)
Antimicrobial peptides are small molecules, up to 10 kDa, present in all kingdoms of life, including in plants. Several studies report that these molecules have a broad spectrum of activity, including antibacterial, antifungal, antiviral, and insecticidal activity. Thus, they can be employed in agriculture as alternative tools for phytopathogen and pest control. However, the application of peptides in agriculture can present challenges, such as loss of activity due to degradation of these molecules, off-target effects, and others. In this context, nanotechnology can offer versatile structures, including metallic nanoparticles, liposomes, polymeric nanoparticles, nanofibers, and others, which might act both in protection and in release of AMPs. Several polymers and biomaterials can be employed for the development of nanostructures, such as inorganic metals, natural or synthetic lipids, synthetic and hybrid polymers, and others. This review addresses the versatility of NanoAMPs, and their potential applications in agribusiness, as an alternative for the control of phytopathogens in crops.